Patient Compliance during 24-Hour Dual pH Probe Monitoring for Extraesophageal Reflux. (11th October 2011) - Musser, Joy; Kelchner, Lisa; Neils-Strunjas, Jean; Montrose, Marshall
Abstract : Objective . During ambulatory 24-hour dual pH probe monitoring for suspected extraesophageal reflux (EER), patients are responsible for indicating relevant study events. Study interpretation relies on patient accuracy and compliance to test instructions. This study sought to explore patient compliance during pH probe monitoring and evaluated the utility of a Post-Evaluation Questionnaire as a clinical tool. Participants and Methods . Participants were prospectively studied during 24-hour dual pH probe monitoring. Participants used both a food diary and monitor settings to indicate relevant study events. Following pH testing, participants completed a Post-Evaluation Questionnaire regarding test experiences. Results . Eighty-two participants completed the study. Means and standard deviations were calculated for individual responses on the Post-Evaluation Questionnaire. Means indicate high participant accuracy for study events, and adherence to typical activities and diet over the testing period. Factor analysis was performed on the Post-Evaluation Questionnaire items and identified two factors: "typical experiences" and "times forgot." Cronbach's alpha demonstrated acceptable reliability levels for questions related to "typical experiences, " but poor reliability for "times forgot" questions. Conclusions . Assessment of participant compliance during pH probe testing can quickly and easily be completed through a Post-Evaluation Questionnaire. Participant compliance can be assessed for improved study interpretation.